Financial Performance of Bank Syariah Indonesia (BSI) Before and After Merger - Bambang Iswanto; Siti Alawiyah; Kokom Komariah; Idhafiyyah Anwar (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2022)
As mergers can play a crucial role in enabling sharia banks to withstand intense competition, assessing their financial performance before and after a merger can provide valuable insights.. Therefore, this study analyzes the financial performance before and after the merger at Bank Syariah Indonesia. In analyzing the data, the comparative descriptive method was used by comparing the financial statements and the Good Corporate Governance report of Bank Syariah Indonesia for one year. The Risk-Based Bank Rating (RBBR) method, which includes four assessment factors, namely Risk Profile, Good Corporate Governance, Earning, and Capital (RGEC), was applied to assess the performance of the bank using NPF, FDR, GCG, ROA, ROE, NIM, BOPO, and CAR ratios. The data analysis used descriptive statistics, Shapiro-Wilk, and Wilcoxon Signed Rank Tests. Based on the analysis, the percentage difference in the BOPO and NIM ratios was the largest and lowest, which were 6.16% and 0.08%. Furthermore, there was a significant difference in the financial performance of Bank Syariah Indonesia before and after the merger, which became increasingly healthy. This study has implications for bank assessment policies, as it highlights the need to consider various factors to assess the output scale produced in the bank.